METHOD OF SEMANTIC DIFFERENTIAL (International Conference on Scientific Research in Natural and Social Sciences, 2025)
The paper presents the results of the pre-research conducted under the project entitled “Seniors in the Eyes of Children”. The main objective of the project was to create and test a research tool in order to establish what the attitudes of pupils to old age and seniors were. Semantic differential was chosen for these purposes. Semantic differential serves to map attitudes, penetrates the deeper layers of thinking, and tries to understand the individual meanings of words and the feelings of respondents. The paper primarily deals with the semantic differential method, the preparation and implementation of the pre-research, the process of creation of the research tool, and the individual steps in the collection and evaluation of data.